Measuring and Evaluation of Particulate Matter in Luang Prabang City - Orphomma, Sounith; Soukhavong , Sengthong; Kounlaxay, Kalaphath (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
This research, there is a purpose to study about intensity quantity of particulate matter less than 10 micrometer such as PM0.3, PM0.5, PM1.0, PM2.5, PM5.0 and PM10. During the people are burning the forest to make rice field and grow the plants and compare with during the forest in not born. Also asses the security level and danger of dust particles measure in Luangprabang city by random sampling from April to July 2018 for three points such as the Souphanouvong monument (Souphanouvong University), Langxang Public Park and night market intersection. The result found that the respirable dust has high intensity quantity during the forest burning such as PM0.3 is value between 106,960 – 474,649 ppm, the average 216,362 ppm. PM0.5 is between 19,028 – 145,214 ppm, the average 59,486, PM2.5 is between 473 – 2,104 ppm, the average 774 ppm. All of three size are over the security standard level (yellow level), the measure PM1.0 average 7,458 ppm, PM5.0 average 80 ppm and PM10 average 35 ppm are in the standard security (green level). The research also mention that three points from sampling witch during burning are the Souphanouvong monument has the highest small dust intensity quantity such as PM0.3, the average of Souphanouvong monument is 273,874 ppm, the average of Langxang Public Park is 24,896 ppm and the average of night market intersection is 240,171 ppm that different from during the forest is not burning as the highest dust value is the night market intersection such as the average of PM0.3 is 60.553 ppm that cause of there is more traffic jam than Langxang Public Park the average 47,328 ppm and Souphanouvong monument average 29,585 ppm; But those values are still in the standard security level.